The link between co-rumination and mood problems in victimized adolescents: A daily diary study - Malamut, Sarah T.; Laninga-Wijnen, Lydia (SAGE, 2026)
This pre-registered daily diary study examined the extent to which daily co-rumination with friends after experiencing victimization may exacerbate victimized youths’ daily mood problems, considering both within- and between-person perspectives. For 15 consecutive school days, n = 1,669 Finnish seventh- to ninth-grade adolescents (Mage = 14.45; 55.5% girl) filled in daily questionnaires about victimization, co-ruminating about victimization, and mood. On the within-person level, students did not experience worse mood on days they were victimized and co-ruminated, compared to days they were victimized and did not co-ruminate about it. On the between person-level, students who were victimized at least once and co-ruminated about it as least once experienced more mood problems as compared to those who were victimized at least once but never talked to friends about their victimization. Sensitivity analyses revealed that when controlling for victimization intensity, co-rumination was associated with benefits in daily mood (i.e., less depressed mood) on the within-person level compared to days in which youth were victimized and talked to a friend but did not co-ruminate.